Shadow vs. market prices in explaining land allocation: subsistence maize cultivation in rural Mexico - Aslıhan Arslan (Kiel Institute for the World Economy (IfW), 2008)
Economic models of land allocation may lead to expectations for farmer response that surprisingly do not materialize, if market prices fail to reflect the value of farmers' product. Shadow prices rather than market prices explain resource allocation better for farmers who attach significant non-market values to their own crops. I extend the theoretical model in Arslan and Taylor (2008) to explain why the land allocation of such farmers may not respond to market signals even if transaction costs are not binding. I estimate the proportion of land subsistence maize farmers allocate to traditional versus modern maize varieties using nationally representative rural household data from Mexico the center of diversity of maize. I conclude that shadow prices explain land allocation better than market prices and discuss the importance of non-market values in understanding both farmers' supply response and on-farm conservation of traditional crops with non-market values.
Keywords: O12; O13; Q12; Q39; 330; Land allocation; shadow prices; non-market values; traditional crops; on-farm conservation; Mexico; Landwirtschaftliche Bodennutzung; Allokation; Maisanbau; Subsistenzwirtschaft; Mais; Schattenpreis; Naturschutz; Mexiko